2008
DOI: 10.1038/eye.2008.19
|View full text |Cite
|
Sign up to set email alerts
|

Origin and turnover of ECM proteins from the inner limiting membrane and vitreous body

Abstract: The inner limiting membrane (ILM) and the vitreous body (VB) are two major extracellular matrix (ECM) structures that are essential for early eye development. The ILM is considered to be the basement membrane of the retinal neuroepithelium, yet in situ hybridization and chick/quail transplant experiments in organcultured eyes showed that all components critical for ILM assembly, such as laminin or collagen IV, are not synthesized by the retina. Rather, ILM proteins, with the exception of agrin, originate from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
56
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 36 publications
5
56
0
Order By: Relevance
“…Previous AFM studies showed that the mechanical strength is in the mPa range, very similar to the articular cartilage and about 1000-fold stronger than cell layers. 18,24,25 Our results underline previous reports 20 describing that the average stiffness of the ILM is over fivefold higher at the retinal side as compared with the vitreal side. This difference nicely explains the fact that the ILM curls up towards its vitreal side after peeling.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Previous AFM studies showed that the mechanical strength is in the mPa range, very similar to the articular cartilage and about 1000-fold stronger than cell layers. 18,24,25 Our results underline previous reports 20 describing that the average stiffness of the ILM is over fivefold higher at the retinal side as compared with the vitreal side. This difference nicely explains the fact that the ILM curls up towards its vitreal side after peeling.…”
Section: Discussionsupporting
confidence: 81%
“…15 Atomic Force Microscopy (AFM) is a well established examination technique that has been used to measure the thickness and rigidity of human ocular basement membranes such as the unstained ILM. 18,19 The aim of the present investigation was to assess and quantify in vitro changes of the ILM of the human retina after staining with either brilliant blue or ICG with and without subsequent illumination using a standard surgical light (PENTA LUX x 50, Ophthalmologische Systeme GmbH Fritz Ruck, Eschweiler, Germany) source compared with unstained ILM using AFM.…”
Section: Introductionmentioning
confidence: 99%
“…These differences may in part reflect the way each basement membrane forms, for example, the radial glial endfeet and the meningeal fibroblasts are thought to deposit the pial basement membrane on the surface of the brain, whereas the ILM forms by the precipitation of matrix proteins from the vitreous; a process thought to allow for the rapid assembly of the ILM during embryonic eye development (Halfter et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A primary role for the CB is secretion of the aqueous humor, and of components of the vitreous and inner limiting membranes. The CB is therefore pivotal to the establishment and maintenance of ocular pressure and to the survival of the GCs (Gould et al, 2004;Halfter et al, 2008;Halfter et al, 2005). The iris is composed of two layers of pigmented epithelium, muscles and stroma (for a review, see Davis-Silberman and Ashery-Padan, 2008).…”
Section: Introductionmentioning
confidence: 99%